2012
DOI: 10.1080/17470218.2011.590595
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus/Response Learning in Masked Congruency Priming of Faces: Evidence for Covert Mental Classifications?

Abstract: Reaction times for categorization of a probe face according to its sex or fame were contrasted as a function of whether the category of a preceding, sandwich-masked prime face was congruent or incongruent. Prime awareness was measured by the ability to later categorize the primes, and this was close to chance and typically uncorrelated with priming. When prime faces were never presented as visible probes within a test, priming was not reliable; when prime faces were also seen as probes, priming was only reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although attention appears to be necessary for masked priming [56,57] , response congruency effects in masked priming suggest that awareness is not necessary for retrieving S–R bindings [58] . Eckstein and Henson [58] , however, found no evidence of response congruency effects for masked primes that were never seen unmasked, suggesting that awareness is necessary for encoding such bindings. Although other studies have found main effects of priming from primes never seen unmasked [32,59–61] , this residual priming could reflect unconscious facilitation of component processes [59,60] rather than subliminal encoding of S–R (or F–R) bindings.…”
Section: Role Of Attention and Awareness At Encoding And Retrievalmentioning
confidence: 96%
See 1 more Smart Citation
“…Although attention appears to be necessary for masked priming [56,57] , response congruency effects in masked priming suggest that awareness is not necessary for retrieving S–R bindings [58] . Eckstein and Henson [58] , however, found no evidence of response congruency effects for masked primes that were never seen unmasked, suggesting that awareness is necessary for encoding such bindings. Although other studies have found main effects of priming from primes never seen unmasked [32,59–61] , this residual priming could reflect unconscious facilitation of component processes [59,60] rather than subliminal encoding of S–R (or F–R) bindings.…”
Section: Role Of Attention and Awareness At Encoding And Retrievalmentioning
confidence: 96%
“…Although attention appears to be necessary for masked priming [56,57], response congruency effects in masked priming suggest that awareness is not necessary for retrieving S–R bindings [58]. Eckstein and Henson [58], however, found no evidence of response congruency effects for masked primes that were never seen unmasked, suggesting that awareness is necessary for encoding such bindings.…”
Section: Role Of Attention and Awareness At Encoding And Retrievalmentioning
confidence: 99%
“…As such, it can be argued that this priming effect is not the consequence of the interaction between different object categories but reflects stimulus‐response binding between the bird category and a “yes” motor response (e.g., Denkinger & Koutstaal, 2009; Eckstein & Henson, 2012; Horner & Henson, 2009). This is probably the case to some extent and the results of the drift diffusion model support this idea showing slower non‐decisional processes in the two incongruent conditions compared to the congruent condition.…”
Section: Discussionmentioning
confidence: 99%
“…The disagreement regarding Klauer’s correction led to the only partial adaptation of their method. While some researchers used this method (Bermeitinger et al, 2012; Eckstein & Henson, 2012; Spruyt et al, 2012), often acknowledging the debate regarding this correction, others use the original Greenwald regression (Lin & Murray, 2013; Naccache & Dehaene, 2001; Reber et al, 2012; Van Opstal et al, 2005) or, most often, rely on an awareness threshold despite the issues it incurs (Shanks, 2017). Here, we propose a new method inspired by Greenwald regression.…”
Section: Bayesian Generative Modelsmentioning
confidence: 99%